2014
DOI: 10.7324/japs.2014.40802
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of PEG-DNA Biocomplexes by FTIR

Abstract: Understanding the mode involved in the binding of certain molecules to DNA is of prime importance, and PEG offers wide-ranging applications in biological, medical and pharmaceutical contexts. FTIR spectroscopy has been used to characterize how the formed biocomplexes bind or dissociate to/from each other between PEG400-ctDNA under different conditions. Characterization and investigation of the effect of incubation time on PEG400-ctDNA biocomplexes formation were studied through spectroscopic technique FTIR. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As can be seen in the spectra, the characteristic bands of phosphate groups of DNA are absent in water, while they appeared in ILs with lower intensity, and hence, it can be concluded that in ILs the interactions between DNA phosphate and PLL retains the structural integrity of DNA. This result found here is similar to the DNA–PEG complex prepared for the gene delivery, where it was proposed that the weak interaction with phosphate groups decreases the chances of nonspecific interactions, which is desirable in gene delivery . Because the condensation of DNA is normally provoked by multivalent cations such as polyamines, positively charged polymers, and peptides .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As can be seen in the spectra, the characteristic bands of phosphate groups of DNA are absent in water, while they appeared in ILs with lower intensity, and hence, it can be concluded that in ILs the interactions between DNA phosphate and PLL retains the structural integrity of DNA. This result found here is similar to the DNA–PEG complex prepared for the gene delivery, where it was proposed that the weak interaction with phosphate groups decreases the chances of nonspecific interactions, which is desirable in gene delivery . Because the condensation of DNA is normally provoked by multivalent cations such as polyamines, positively charged polymers, and peptides .…”
Section: Resultssupporting
confidence: 85%
“…This result found here is similar to the DNA−PEG complex prepared for the gene delivery, where it was proposed that the weak interaction with phosphate groups decreases the chances of nonspecific interactions, which is desirable in gene delivery. 42 Because the condensation of DNA is normally provoked by multivalent cations such as polyamines, positively charged polymers, and peptides. 43 Herein, the condensation of DNA might have happened due to the presence of PLL in IL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is obtained that the n rises with the rising of the content of Ag NPs. This action due to the rise of the density of nanocomposites [23].…”
Section: -Results and Discussionmentioning
confidence: 99%